The Influence of Brand Experience, Brand Trust on Brand Loyalty (Case Study of Silungkang Art Center) - Haq, Chairul; Nova, Siska Mitra; Hanafi, Hanafi; Saputra, Nefri Anra; Victory, Well (Institut Seni Indonesia Padang Panjang, 2025)
The Silungkang Art Center is a commercial hub that offers various Minangkabau handicrafts produced by local artisans. The purpose of this study is to explore: (1) the influence of brand experience on consumer brand loyalty, and (2) the influence of brand trust on brand loyalty at the Silungkang Art Center. The study is conducted using an explanatory design to identify causal relationships among variables, supported by a quantitative approach and statistical analysis. The empirical evidence suggests that brand experience (BE) has a positive association with brand trust (BT), as indicated by an initial sample estimate value of 0.756081. Furthermore, brand trust (BT) positively influences brand loyalty (BL), with an initial sample estimate value of 0.470450. These findings demonstrate that both brand experience and brand trust play significant roles in strengthening consumer brand loyalty toward the Silungkang Art Center.